INTEGRATING KNOWLEDGE MANAGEMENT AND CHANGE: EXPLORING SECI MODEL APPLICATIONS IN SME’s AND MODERN ORGANIZATIONS - Ritonga, Ricky Rafii; Ernanda, Yovie; Simbolon, Safii (Universitas Dharmawangsa, 2024)
Knowledge management is a crucial element in ensuring organizational sustainability amid rapid changes. The SECI framework (Socialization, Externalization, Combination, Internalization) provides a strategic approach to creating, managing, and utilizing knowledge to support organizational transformation. This paper explores the application of the SECI model in knowledge management, the handling of tacit and explicit knowledge, and the role of technology as a catalyst for change. Through case studies of manufacturing companies, batik-based SMEs, and educational technology start-ups, the paper demonstrates how effective knowledge management enhances operational efficiency, drives innovation, and strengthens competitiveness. Furthermore, it offers practical recommendations for large organizations, SMEs, academia, and governments to adopt sustainable knowledge management strategies. The findings emphasize that integrating the SECI model with modern technology, supported by cross-sector collaboration, enables organizations to adapt and innovate in the face of change. Knowledge management serves not only as an internal organizational asset but also as a strategic tool for creating value and delivering positive impacts for both organizations and society.